Integrating Drama To Speaking Skills In English Learning : A Systematic Review - Nindy Ganap, Nindy Ganap (KALAO'S MARITIME JOURNAL, 2021)
Drama is one of the language teaching techniques that can be integrated with speaking skills in learning English. This systematic review reviews the four studies that have been carried out in the last five years by including context, participants, methodology, focus, and main findings in the discussion. This review also aims to examine the integration of drama with speaking skills in learning English. The participants used as samples in this study came from high school students and also students in the English department in Thailand, Vietnam and Indonesia. Data collection techniques used are qualitative and quantitative, but tend to be more dominant quantitatively. In quantitative data collection, pre and post tests are used. Whereas in qualitative data collection interviews and questionnaires were used. The focus of this review is to find a correlation among the results of the previous studies. Finally, this review recommends drama as a very useful teaching technique to be applied in learning English especially for developing students' speaking skills.